Islam and Civil Society: A Study of Azyumardi Azra's Thoughts in Building a Cultural Movement in Indonesia - Siswanto, M.; Muizudin, Muizudin; Kazhimi, Ahmad Bagus (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
The tap for democracy in Indonesia only opened quite wide when government leadership shifted from Soeharto to Gus Dur. This marks the emergence of a cultural movement by a group of people in various regions. This research aims to find answers to how the civil society movement model is relevant in the Indonesian context and the power of civil society to realize political decency. The method used in this research is descriptive-analytic based on literature review of various existing literature (library research). From the research carried out, it was found that the term civil society in Islam is equivalent to civil society. Civil society refers to the historical and socio-political context established by the Prophet Muhammad SAW and his followers in Medina. Azra sees civil society as a civil society that is independent, democratic, religious, civilized and upholds human values. In the Indonesian context, civil society is an alternative solution to social problems through empowering and strengthening the control power of civil society so that it is able to realize and uphold democratic life and uphold human rights.